Delimitação específica e filogeografia do complexo Protium aracouchini (Aubl.) Marchand (Burseraceae) - Perdiz, Ricardo de Oliveira (Botânica, 2020)
The Protium aracouchini (Aubl.) Marchand species complex (PASC) encompasses eight species that occur in the Amazon Basin, on the Guiana Shield, on the Andes, in the Cerrado, and in the Atlantic Forest. This work presents the results of an integrative investigation using molecular, spectral, and morphological data in order to reconstruct the phylogeographical history of the PASC by using different analyses that allow a better delimitation of all species that belong to this complex, and to the elucidation of the historical processes directing their diversification. Specific questions aimed to: (1) reconstruct the evolutionary history of the PASC through a phylogeographical approach, investigating what is the demographic history of expansion and contraction of the populations of the complex through space and time, and its relationship to the geological and climatic events in South America over the past 15 million years; (2) revise the species delimitation and the taxonomy of the PASC; (3) investigate the importance of ecological specialization in the diversification of the lineages of the complex. We present the results of our analyses in three chapters. In the first chapter, we present the molecular phylogeny of the group and we propose a hypothesis of phylogenetic relationships within the complex alongside species delimitation tests; we also describe four new species (P. apostoloanum sp. nov., P. linguipetalum sp. nov., P. makunaimae sp. nov., and P. vicentinii sp. nov.), that arose after the latter analyses. In the second chapter, we focus on the biogeographical history of the complex, through the inference of a dated phylogeny and answer questions related to specific objectives 2 and 3. In the third chapter, we describe a new species of Protium, P. santamariae, endemic to Costa Rica and sharing greater affinity with species of the Protium heptaphyllum (Aubl.) Marchand species complex, because until this study it was thought that this new species held a closer morphological and phylogenetic relationship to the PASC, a hypothesis that was falsified with the results of chapter 1. Finally, we present a synthesis of our results with the conclusion chapter.
Keywords: Delimitação de espécies; Filogeografia; Revisão taxonômica